Behavioral Responses to Local Tax Rates: Quasi-Experimental Evidence from a Foreigners' Tax Scheme in Switzerland - Kurt Schmidheiny; Michaela Slotwinski (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study behavioral responses to local income taxes exploiting a special tax regime which applies to foreign employees residing in Switzerland. The used institutional setting generates two thresholds through which locally heterogeneous taxation is assigned: An income threshold at 120,000 Swiss francs and a duration threshold at 5 years of stay in Switzerland. We exploit these thresholds by applying a discontinuity in density design and a fuzzy RDD to administrative income data. We find causal evidence for strategic income bunching for wage earners and tax induced intra-national mobility. Several pieces of evidence suggest that individuals have to “learn the tax code” and that knowledge and information transmission through local networks plays a major role in the behavioral response to tax incentives.
Keywords: H24; H31; J61; 330; income bunching; tax induced mobility; income taxes; regression discontinuity design